Challenges and Opportunities in Implementing Social Accounting: Insights from Non-Profit Organizations - Wahyuni, Wahyuni; Toatubun, Warda; Papalia, Sakina; Anggraini, Ratnadila (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study explores the challenges and opportunities non-profit organizations (NPOs) face in implementing social accounting, focusing on organizations operating in resource-constrained environments, particularly in developing countries. The research aims to identify barriers such as financial limitations, lack of expertise, and cultural differences while examining the potential of technological innovations and international collaborations to overcome these challenges. Research Design and Methodology: A qualitative research design using a systematic literature review was employed to gather insights from existing studies on social accounting practices within NPOs. The analysis focused on identifying common themes and emerging trends that inform the implementation of social accounting in different organizational and regional contexts. Findings and Discussion: The findings reveal that NPOs face significant obstacles, particularly in terms of financial resources and access to skilled personnel for social accounting. Cultural and regional factors also play a role in the varying levels of adoption. However, the study highlights the opportunities provided by technological innovations such as AI, cloud-based systems, and Big Data, as well as the benefits of international collaborations in enhancing transparency and accountability. Implications: The study provides practical recommendations for NPO leaders, emphasizing the need for capacity building, technological adoption, and strategic partnerships to improve social accounting. It also calls for developing standardized reporting frameworks to ensure consistency and comparability across the sector.